A new species, Simulium (Nevermannia) berchtesgadense (Diptera: Simuliidae), and its chromosomes, from the Alps of southeastern Germany - Seitz, Gunther; Adler, Peter H.; Forster, Mira (Zootaxa, 2015)
Simulium (Nevermannia) berchtesgadense nov. spec. is described from the Alps of southeastern Germany. The morphology and diagnostic characters for all life stages except the egg are given, and the polytene chromosomes are compared with those of other members of the Simulium (Nevermannia) vernum group. The species is chromosomally similar to Simulium (Nevermannia) cryophilum cytoform 'A' but differs morphologically in each life stage. Bionomic information and the associated simuliid fauna are presented.